Penerapan Graf Berarah dan Berbobot untuk Mengetahui Inluencer yang Paling Berpengaruh dalam Penyebaran Informasi pada Twitter - Rafi' Addani, Aisyah; Turmudi, Turmudi; Sujarwo, Imam (Jurnal Riset Mahasiswa Matematika, 2023)
A graph is a non-empty set whose members are vertices and edges, where the edges connect several pairs of these vertices; likewise, social media connects users with each other through interests, relationships, likes and dislikes. The rapid development of technology in the era of globalization has made social media a more effective source of information, one of them is Twitter which has been used by 280 million people in the world. This research involves 100 Twitter users who are classified as Influencers in Indonesia who have more than 10,000 followers by visualizing their relationship with other users followed by them with a directed and weighted graph. First, the data is filtered using the Twecoll script in Python software, then the data is visualized using the Gephi software in the form of a directed and weighted graph. The centrality value is calculated to determine the influential influencers in spreading information on the network. Based on the results of the study, it was found that the network pattern of 100 Influencers that had been collected in the following list of @dearmyths accounts, there were 96 points and 1883 sides with the side having the highest weight being @detikcom, followed by @ivanlanin and @ernestprakasa through the results of centrality calculations as accounts that can disseminate information on the network.